Laboratory surveillance of bacterial gastroenteric pathogens in The Netherlands, 1991-2001. - van Pelt, W. (Cambridge University Press, 2003)
Results of the Dutch laboratory surveillance of bacterial gastroenteritis between 1991 and 2001 are presented and compared with recent findings in general practices and in the community. Between 1996 and 2000 the mean annual number of stools screened by sentinel laboratories was about 1000 samples/100,000 inhabitants, which is 4% of the estimated annual incidence of gastroenteritis in the Dutch population. Campylobacter (36/100,000 inhabitants) and salmonella (24/100,000 inhabitants) were the main pathogens isolated. Since 1996, the incidence of laboratory confirmed salmonellosis decreased by 30%, predominantly among young children. The incidence of campylobacter was highest in urban areas and Salmonella Enteritidis emerged as the predominant serotype in urban areas. Between 1991 and 2001, multi-resistant Salmonella Typhimurium DT104 emerged to comprise up to 15% of all salmonella isolates in 2001. Reported rates of Shigella spp. and Yersinia spp. varied little, with average annual incidences of 3.2 and 1.2 cases/100,000 inhabitants, respectively. Escherichia coli O157 (90% STEC) was scarcely found (0.26/100,000).